2015
DOI: 10.24095/hpcdp.35.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome and fibromyalgia in Canada: prevalence and associations with six health status indicators

Abstract: Introduction Few studies have considered the factors independently associated with chronic fatigue syndrome (CFS) and/or fibromyalgia (FM) or considered the impact of these conditions on health status using population-based data. Methods We used data from the nationally representative 2010 Canadian Community Health Survey (n= 59 101) to describe self-reported health professional-diagnosed CFS and/or FM, and their associations with 6 health status indicators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 20 publications
5
46
0
4
Order By: Relevance
“…For example, Rusu et al 4 reported no association between CFS and obesity in a large sample of Canadian adolescents and adults. In another large cohort study, Viner et al 1 observed no association between the prevalence of obesity and the less severe diagnosis of persistent fatigue in 1880 adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rusu et al 4 reported no association between CFS and obesity in a large sample of Canadian adolescents and adults. In another large cohort study, Viner et al 1 observed no association between the prevalence of obesity and the less severe diagnosis of persistent fatigue in 1880 adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Another observation that may support this theory is that smokers reported more fatigue than nonsmokers. Others have also reported this association . Smoking causes oxidative stress, with subsequent increases of antioxidative defence and other mechanisms to protect cellular life.…”
Section: Discussionmentioning
confidence: 75%
“…Others have also reported this association. 33 Smoking causes oxidative stress, with subsequent increases of antioxidative defence and other mechanisms to protect cellular life. Fatigue is associated with oxidative stress in many chronic inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Fatigue Syndrome (also known as Myalgic Encephalomyelitis, hereafter referred to as ME/CFS) is a canonical example of a complex, multifactorial disease with symptoms that can vary substantially between patients. ME/CFS is a debilitating multisystem disease affecting millions to tens of millions of people globally [1][2][3][4][5][6], with an annual economic impact between $17 and $24 billion [7]. Yet the biological basis of ME/CFS remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%